An Analysis Of The Commonest Content Transfer Problems From English Manuscript Into Indonesian Subtitle In Ramona And Beezus Move - PRIMADEVI , SABILLA (2012)
The research discusses three objectives of the study: 1) to classify the commonest content transfer problems, 2) to clarify the change of meaning or not, and 3) to clarify the change of structural form or not in movie manuscript and its subtitle. The writer uses the theory by Nida and Taber (1969) in order to know the commonest content transfer problems and the structural adjustment. This research uses descriptive qualitative approach. The data are taken from Ramona and Beezus movie manuscript and its subtitle. The total data are eighty-four. The analysis used in this research is comparative study between English manuscript and Indonesian subtitle. The results of this research paper are: 1) the commonest content transfer problems involve idioms (21.43%), figurative meanings (5.95%), shifts in central component meaning (23.81%), pleonastic expressions (14.29%), formulas (11.90%), redistribution of semantic components (10.71%), and provision of contextual conditioning (3.57%); 2) the effects are meaning change (30.95%) and no meaning change (69.04%); 3) the structural form involves sentence structure (98.81%) and corresponding sound (1.19%).